Phenol-Rich Compounds Sweet Gel: A Statistically More Effective Antibiotic than Cloxacillin Against Pseudomonas Aeruginosa - Mehrab Dashtdar; Mohammad Reza Dashtdar; Babak Dashtdar; Gazala Afreen Khan; Karima Kardi (Korean Pharmacopuncture Institute, 2016)
Objectives: The purpose of this study was to obtain a natural antibiotic from Phenol-rich compounds; for the dressing and the treatment of chronic wounds. Methods: The Phenol-rich compound sweet gel was prepared by blending four natural herbal extracts, Acacia catechu (L.F.), Momia (Shilajit),